1984
DOI: 10.1002/ajmg.1320170207
|View full text |Cite
|
Sign up to set email alerts
|

Terminal and interstitial deletions of the long arm of chromosome 7: A review with five new cases

Abstract: Sixteen cases of terminal deletions and 17 cases of interstitial deletions of the long arm of chromosome 7 have been reported to date. We present two new cases of the former and three of the latter. The somatic changes in these patients are tabulated and an update on the anomalies associated with the various cytogenetic entities is presented. Changes found in over one-third of patients with 7q terminal deletion syndrome include: developmental delay, pre- and postnatal growth retardation, generalized hypotonia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 24 publications
(30 reference statements)
1
42
0
Order By: Relevance
“…The patients with less deleted material from 7q35~qter resemble quite closely to the phenotype of the patients with monosomy of 7q32--*qter (Kodama et al, 1980;Young et al, 1984). The clinical features, especially facial appearance including SMCI, of our two patients apparently differ from those of the patients with a terminal deletion of 7q distal to q35 (Francke, 1978;Lambert et al, 1981;Turleau et al, 1979;Young et al, 1984). It might imply that 7q35 is the critical segment compatible with typical terminal 7q-syndrome, and that at/east one of the genes influencing the occurrence of SMCI is located on 7q36.1~qter.…”
Section: Discussionmentioning
confidence: 58%
“…The patients with less deleted material from 7q35~qter resemble quite closely to the phenotype of the patients with monosomy of 7q32--*qter (Kodama et al, 1980;Young et al, 1984). The clinical features, especially facial appearance including SMCI, of our two patients apparently differ from those of the patients with a terminal deletion of 7q distal to q35 (Francke, 1978;Lambert et al, 1981;Turleau et al, 1979;Young et al, 1984). It might imply that 7q35 is the critical segment compatible with typical terminal 7q-syndrome, and that at/east one of the genes influencing the occurrence of SMCI is located on 7q36.1~qter.…”
Section: Discussionmentioning
confidence: 58%
“…Crawfurd et al (1979) reported a patient with a karyotype of 46,XY,del (7) (q11q21), who showed developmental delay, hypotonia, and infantile spasms. Young et al (1984) reported a 10-year-old girl who suffered recurrent pneumonia, growth deficiency, severe psychomotor delay, and seizures, with an EEG showing hypsarrhythmia. Her karyotype was 46,XX,del (7) (q11.21q21.11).…”
Section: Discussionmentioning
confidence: 99%
“…Seizures were described in 14 cases. No specific common region stood out; seizures were described in deletions of various sizes, extending from the pericentromeric region to the terminal region (91)(92)(93)(94)(95)(96)(97)(98)(99).…”
Section: Deletion Of the Long Arm Of Chromosomementioning
confidence: 99%
“…Seizure onset ranged from the neonatal period to 7 years (91,97). Febrile convulsions alone occurred in four cases (91,92,96,98), generalized seizures in three (94,95,97), myoclonic seizures in one (93), and a combination of afebrile and febrile seizures in one case (93). Two cases of Williams syndrome del(7)(q11.23), have been described with infantile spasms (100), but seizures are rare in this disorder.…”
Section: Deletion Of the Long Arm Of Chromosomementioning
confidence: 99%